Microbes for climate resilient agriculture - Kashyap, Prem Lal, 1981-; Srivastava, Alok Kumar, 1968-; Tiwari, Shree Prakash; Kumar, Sudheer, 1972- (Hoboken, NJ : John Wiley & Sons, Inc., 2018)
'Microbes and climate are major influences on crop growth, and therefore significantly influence the quality, productivity, and sustainability of food production systems. Global warming is projected to significantly impact agriculture in terms of temperature, precipitation, chilling and glacial run-off etc. Microbes can be both beneficial and detrimental in agriculture; the array of functions they perform under stressed/limited conditions are currently underestimated. Agriculture is affected by the crop microbiome, nutrient cycling microbes, endophytes, and mycorrhizae, as well as pests and disease. Agricultural sustainability has always been highly dependent on the relationships between these factors. Various microorganisms can thrive under extreme conditions - extreme temperatures, extreme pH, high saline concentrations and pressures, etc. As a result, they provide excellent models for understanding the stress tolerance, adaptation and response mechanisms that can be subsequently engineered into crop plants to cope with climate change induced stresses. Use of these microorganisms may alleviate stresses in crop plants, which in turn opens a new and emerging application in agriculture. While there is an abundance of information on this topic, there is not yet a comprehensive volume pulling current research together. This text will be authored by leaders in the field and edited to ensure conciseness and clarity. Chapters will cover a broad range of agriculturally important crops, impact of climate change on crops as well as biotechnologically and environmentally relevant microbes; the text will serve as a springboard for novel research findings and new applications in the field'--Provided by publisher.
Conservation agriculture for climate change resilience : a microbiological perspective / Raj Pal Meena and Ankita Jha -- Archaeal community structure : resilience to climate change / Manesh Thomas, K.K. Pal, and Rinku Dey -- Mycorrhiza -- helping plants to navigate environmental stresses / Raghvendra Pratap Singh, Geetanjali Manchanda, Mian Nabeel Anwar, Jun Jie Zhang, and Yue Zhang Li -- Endophytic microorganisms : future tool to climate resilient agriculture / R. Dey, Kamal Krishna Pal, Thomas M., D.N. Sherathia, V.B. Mandaliya, R.A. Bhadania, M.B. Patel, P. Maida, D.H. Mehta, B.D. Nawade V. Patel -- Bacillus thuringiensis : genetic engineering for insect pest management / Gothandapani Sellamuthu, Prabhakaran Narayanasamy, and Jasdeep Chatrath Padaria -- Microbial nanotechnology for climate resilient agriculture / Prem Lal Kashyap, Shikha Sharma, Poonam Jasrotia, Sudheer Kumar, Alok Kumar Srivastava.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 05, 2018).
Keywords: Agricultural microbiology; Sustainable agriculture; BUSINESS & ECONOMICS -- Industries -- General; Agricultural microbiology; Sustainable agriculture; Agriculture -- methods; Climate change; Microbiota; Biotechnology; Food supply; Electronic books